Discovering the Hidden Secrets in Your Data - the Data Mining Approach to Information - Michael Lloyd-Williams (Information Research: An International Electronic Journal)
Nowadays, digital information is relatively easy to capture and fairly inexpensive to store. The digital revolution has seen collections of data grow in size, and the complexity of the data therein increase. Advances in technology have resulted in our ability to meaningfully analyse and understand the data we gather lagging far behind our ability to capture and store these data . It is often the case that large collections of data, however well structured, conceal implicit patterns of information that cannot be readily detected by conventional analysis techniques . Such information may often be usefully analysed using a set of techniques referred to as knowledge discovery or data mining. These techniques essentially seek to build a better understanding of data, and in building characterisations of data that can be used as a basis for further analysis, extract value from volume. This paper describes a number of empirical studies of the use of the data mining approach to the analysis of health information.